Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Gọi \(k=\frac{a}{b}=\frac{c}{d}\)
\(\Rightarrow\)a=kb ; c=kd
\(\Rightarrow\frac{a+c}{b+d}=\frac{bk+dk}{b+d}=\frac{k\left(b+d\right)}{b+d}=k\)
Vậy...
Ta có : \(\hept{\begin{cases}b^2=ac\\c^2=bd\end{cases}\Rightarrow\hept{\begin{cases}b.b=a.c\\c.c=b.d\end{cases}\Rightarrow}\hept{\begin{cases}\frac{a}{b}=\frac{b}{c}\\\frac{b}{c}=\frac{c}{d}\end{cases}\Rightarrow}\frac{a}{b}=\frac{b}{c}=\frac{c}{d}\Rightarrow\frac{a^3}{b^3}=\frac{b^3}{c^3}=\frac{c^3}{d^3}=\frac{a^3+b^3+c^3}{b^3+c^3+d^3}}\)
=> \(\frac{a^3}{b^3}=\frac{a^3+b^3+c^3}{b^3+c^3+d^3}\)(1)
mà \(\frac{a^3}{b^3}=\left(\frac{a}{b}\right)^3=\frac{a}{b}.\frac{a}{b}.\frac{a}{b}=\frac{a}{b}.\frac{b}{c}.\frac{c}{d}=\frac{abc}{bcd}=\frac{a}{d}\)(2)
Từ (1) và (2) => đpcm
Đặt \(\frac{a}{b}=\frac{c}{d}=k\)\(=>\hept{\begin{cases}a=b.k\\c=d.k\end{cases}}\)
\(\left(\frac{a-b}{c-d}\right)^2=\left(\frac{b.k-b}{d.k-d}\right)^2=\left(\frac{b.\left(k-1\right)}{d.\left(k-1\right)}\right)^2\)\(=\frac{\left(b^2.\left(k-1\right)^2\right)}{\left(d^2.\left(k-1\right)^2\right)}=\frac{b^2.\left(k-1\right)^2}{d^2.\left(k-1\right)^2}=\frac{b^2}{d^2}\)\(\left(1\right)\)
\(\frac{ab}{cd}=\frac{b.k.b}{d.k.d}=\frac{b^2.k}{d^2.k}=\frac{b^2}{d^2}\left(2\right)\)
Từ (1) và (2) => \(\left(\frac{a-b}{c-d}\right)^2=\frac{ab}{cd}\)
Đặt \(\frac{a}{b}\)= \(\frac{c}{d}\)= k => a= bk ; c = dk
\(\frac{\left(a-b\right)^2}{\left(c-d\right)^2}\) = \(\frac{\left(bk-b\right)^2}{\left(dk-d\right)^2}\)= \(\frac{b^2.\left(k-1\right)^2}{d^2.\left(k-1\right)^2}\)= \(\frac{b^2}{d^2}\) (1)
\(\frac{ab}{cd}\)= \(\frac{bk.b}{dk.d}\)= \(\frac{b^2}{d^2}\) (2)
Từ (1) và (2) ->> \(\frac{\left(a-b\right)^2}{\left(c-d\right)^2}\) = \(\frac{ab}{cd}\)
Đặt \(\frac{a}{b}=\frac{c}{d}=k\Rightarrow a=bk,c=dk\)
\(\frac{a^3+b^3}{c^3+d^3}=\frac{\left(bk\right)^3+b^3}{\left(dk\right)^3+d^3}=\frac{b^3\left(k^3+1\right)}{d^3\left(k^3+1\right)}=\frac{b^3}{d^3}\)
\(\frac{a+b^3}{c+d^3}=\frac{bk+b^3}{dk+d^3}\)
Đề bài sai nhé bạn
Ta có:
\(b^2=ac\Rightarrow\frac{a}{b}=\frac{b}{c}\)
\(c^2=bd\Rightarrow\frac{b}{c}=\frac{c}{d}\)
\(\Rightarrow\frac{a}{b}=\frac{b}{c}=\frac{c}{d}\Rightarrow\frac{a^3}{b^3}=\frac{b^3}{c^3}=\frac{c^3}{d^3}\)
Ta có : \(b^2=ac\)
\(\Rightarrow\frac{a}{b}=\frac{b}{c}\) (1)
\(c^2=bd\)
\(\Rightarrow\frac{b}{c}=\frac{c}{d}\) (2)
Từ (1) và (2) suy ra : \(\frac{a}{b}=\frac{b}{c}=\frac{c}{d}\)
\(\Rightarrow\frac{a}{b}.\frac{a}{b}.\frac{a}{b}=\frac{a}{b}.\frac{b}{c}.\frac{c}{d}\) , \(\frac{b}{c}.\frac{b}{c}.\frac{b}{c}=\frac{a}{b}.\frac{b}{c}.\frac{c}{d}\) và \(\frac{c}{d}.\frac{c}{d}.\frac{c}{d}=\frac{a}{b}.\frac{b}{c}.\frac{c}{d}\)
\(\Rightarrow\frac{a^3}{b^3}=\frac{a}{d}\) , \(\frac{b^3}{c^3}=\frac{a}{d}\) và \(\frac{c^3}{d^3}=\frac{a}{d}\)
\(\Rightarrow\frac{a^3}{b^3}=\frac{b^3}{c^3}=\frac{c^3}{d^3}=\frac{a}{d}\)
\(\Rightarrow\frac{a^3}{b^3}=\frac{b^3}{c^3}=\frac{c^3}{d^3}=\frac{a}{d}=\frac{a^3+b^3+c^3}{b^3+c^3+d^3}\)
Vậy \(\frac{a}{d}=\frac{a^3+b^3+c^3}{b^3+c^3+d^3}\)
\(\frac{a+b}{b+3}=\frac{3+d}{d+a}=\frac{a+b+3+d}{b+3+d+a}=1\Rightarrow a+b=b+3\Rightarrow a=3\)